A Radical and Progressive Legacy: Labour's Housing Record, 1945 to 1951. Issue 1 (1st April 2022) - Temple, John Robert
Abstract : The housing record of the Labour governments of 1945 to 1951 has traditionally been described as both an underachievement and the welfare state failure of Labour and Aneurin Bevan. This judgement has been reached by way of a focus on quantitative performance indicators; that is, on the number of permanent houses constructed during the period. Given the acute housing shortage following the end of the Second World War and housing's premier position on the list of priorities of the British public, such a judgement, made on quantitative terms alone, is not without foundation. Ernest Bevin's staggering claim during the 1945 election campaign that Labour would build four to five million houses 'in quick time', and similar rhetoric from other senior Labour figures, only served to raise public expectations about Labour's housing ambitions. This article argues that Labour's post-war housing record, if assessed on the basis of both the quantity and the quality of the houses constructed, in addition to the political ideology that underpinned Labour's housing programme, far from being one of underachievement and failure, was one of radical and progressive achievement.